hermostability of protein in starch derivative emulsion - Siti Suhairah, Omar (2013)
Heat-induced destabilisation (denaturation) of whey proteins (WP) is one of the major problems limiting their application in food products. Microencapsulation is a relatively new technology that is used for protection and stabilization. The purpose of this research is to determine the protein denaturation kinetic rate order for main fractions of whey protein isolate (WPI) that are β-lactoglobulin (β-Lg) ,α-lactoalbumin (α-Lac) and bovine serum albumin (BSA). The other purpose of this research is to formulate the microencapsulation material. This method is used to minimize the denaturation of the protein. The experiment was conducted start from preparation sample of various composition of whey protein - maltodextrin solution for heating process (water bath and oil bath). Next step is the preparation of sample for further analysis in UPLC. During kinetic denaturation analysis, the parameter was use are temperature, time and via microencapsulation technique. From the research, the best ratio for WPI and maltodexrtrin is 9:1. The percentage denaturation for 9:1 of WPI to maltodextrin ratio is lower compared to the ratio 1:1. Results from analysis of composition of the residual native protein suggested that thermal sensitivity of a-lac is lower than B-lg. The percentage of denaturation of B-lg is faster than a-lac for each temperature with increasing time. High temperature will cause high percentage of denaturation. The temperature 60⁰C shows the lowest percentage of denaturation as showed in Figure 4.13 and 4.14. In conclusion, result from this research may be useful to gain understanding of relationship between heat treatment and its effect on functional properties of whey protein.